1997
DOI: 10.1074/jbc.272.14.9464
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ca2+ Pool Content and Signaling and Expression of a Calcium Pump Are Linked to Virulence in Leishmania mexicana amazonesis Amastigotes

Abstract: Virulent and avirulent clones of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 64 publications
8
90
0
1
Order By: Relevance
“…1, B and C). When each ionophore was present throughout excystation, the IC 50 for ionomycin was 38 nM and for A23187 the IC 50 was 126 nM. The idea that these inhibitors were acting specifically was supported by 45 Ca uptake studies (data not shown).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…1, B and C). When each ionophore was present throughout excystation, the IC 50 for ionomycin was 38 nM and for A23187 the IC 50 was 126 nM. The idea that these inhibitors were acting specifically was supported by 45 Ca uptake studies (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…The IC 50 for TG when present throughout excystation was 7 M. TG at 10 M significantly inhibited giardial excystation only during Stage II (Fig. 3).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The best preservation was obtained with high-pressure freezing followed by freeze substitution, revealing a very electron-dense aspect. Acidocalcisomes were detected in several protozoa: T. brucei (Vercesi et al 1994), T. cruzi (Docampo et al 1995), L. amazonensis (Lu et al 1997), Toxoplasma gondii (Moreno & Zhong 1996) and Plasmodium falciparum (Marchesini et al 2000). Biochemical data obtained from digitonin-permeabilized cells indicated the presence of a bafilomycin A-sensitive H + -ATPase and a vanadate-sensitive Ca 2+ pump in the acidocalcisome.…”
Section: Isolation Of the Acidocalcisomementioning
confidence: 99%